Android-Based Media Development in Mathematics Lessons - Firdayati, Ulfi; Darwan, Darwan; Kusmanto, Hadi (EduMa: Mathematics education learning and teaching, 2021)
This study aims to develop Android-based media for learning the orm applications by developing designs to attract students to learn independently. The application used in this study is the Smart Apps Creator (SAC). This media development uses the research and development (R&D) method according to Sugiyono by using the Potential and Problem steps, Gathering Information, Product Design, Design Validation, Design Improvement, Product Testing, Product Revision, and Usage Trials. The validation results by the media expert were 0.84 with the criteria "Very Appropriate." The validation results by the material experts were 0.80 with the criteria "Very Suitable." Based on the results of expert validation, the application is declared valid and feasible to be tested on a limited and broad basis. Based on the limited trial results and broadly obtained from the results of the questionnaire for each item number> 50%. To sum up,Â  that this android-based mathematics application media is suitable for independent learning wherever and wheneverÂ